The receptor for advanced glycation end products is a sensor for cell‐free heme. (29th December 2020) - May, Olivia; Yatime, Laure; Merle, Nicolas S.; Delguste, Florian; Howsam, Mike; Daugan, Marie V.; Paul‐Constant, Charles; Billamboz, Muriel; Ghinet, Alina; Lancel, Steve; Dimitrov, Jordan D.; Boulanger, Eric; et al.
Abstract : Heme's interaction with Toll‐like receptor 4 (TLR4) does not fully explain the proinflammatory properties of this hemoglobin‐derived molecule during intravascular hemolysis. The receptor for advanced glycation end products (RAGE) shares many features with TLR4 such as common ligands and proinflammatory, prothrombotic, and pro‐oxidative signaling pathways, prompting us to study its involvement as a heme sensor. Stable RAGE‐heme complexes with micromolar affinity were detected as heme‐mediated RAGE oligomerization. The heme‐binding site was located in the V domain of RAGE. This interaction was Fe 3+ ‐dependent and competitive with carboxymethyllysine, another RAGE ligand. We confirmed a strong basal gene expression of RAGE in mouse lungs. After intraperitoneal heme injection, pulmonary TNF‐α, IL1β, and tissue factor gene expression levels increased in WT mice but were significantly lower in their RAGE −/− littermates. This may be related to the lower activation of ERK1/2 and Akt observed in the lungs of heme‐treated, RAGE −/− mice. Overall, heme binds to RAGE with micromolar affinity and could promote proinflammatory and prothrombotic signaling in vivo, suggesting that this interaction could be implicated in heme‐overload conditions. Abstract : Free heme interaction with TLR4 does not fully explain its deleterious effects, prompting us to study the involvement of RAGE, another pattern recognition receptor. We demonstrated heme is a RAGE ligand, binding to the V domain and inducing its oligomerization. The interaction strength mainly resides in the chelation of the iron ion. In RAGE −/− mice, proinflammatory pulmonary responses to heme appear attenuated, suggesting a role of this receptor in heme‐overload diseases.